In-company trainers in IVET in figures - Bahl, Anke [Verfasser]; Schneider, Verena [Verfasser] (My University, 2022)
"In-company trainers play a key role in training apprentices at the workplace. Despite the group’s system relevance for initial vocational education and training (IVET) in the German dual system, there are major gaps in the statistics. This article examines existing data and highlights possible ways to improve the data basis." (authors' abstract; BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; P 3.2.1 Ausbilder; 370; Bildungspersonal; Ausbilder; Berufsbildungsstatistik; Quantitative Angaben